UJI AKTIVITAS DIURETIK INFUSA KUMIS KUCING (Orthosiphon stamineus Benth.) PADA TIKUS PUTIH JANTAN (Rattus Norvegicus) GALUR WISTAR - Suharyanisa; Rosina Sitohang; Br purba, Hana Ike Dameria; Sulisty, Yenni (Universitas Sari Mutiara Indonesia, 2020)
Diuretics are substances that can increase urinary output (diuresis) through direct action on the kidneys. Diuretics can also reduce electrolyte reabsorption in the renal tubules by involving active transport processes The cat's whiskers plant contains polymethoxylated flavonoid compounds, phenylpropanoids (caffeic acid derivatives), and terpenoids (especially diterpenes and triterpenes). IDKK was obtained from the infusion technique with distilled water and then the infusion was used on 25 diuretic rats which were divided into 5 groups. Group I (negative) Na-CMC 0.5%, group II (positive) Furosemide 3.6 mg/kgBB, and group III, IV, and V IDKK doses of 10, 20, and 40% were given orally. Rats were given aqua dest orally at a 15 ml/kg BW dose. Mice were placed in metabolic cages, then the physical examination of urine was carried out every 1 hour for 6 hours. The results showed that the IDKK with the best dose was 40%, which increased urine volume, affect urine pH, affect urine specific gravity, and affect the color of urine and the clarity of urine.